Service Quality and Perceived Platform Error Exposure in Digital Learning Platforms: An Extended SEM Study of Perceived Value and Continuance Intentions in Indonesia and Malaysia - Zhuofan Chen; Sin Yin Teh; Theam Foo Ng (International Journal of Environment, Engineering and Education, 2026)
Digital learning platforms have become essential academic service systems in higher education, yet e-learning continuance research has largely emphasized positive quality attributes while under examining recurring technical disruptions. This study investigates how service quality and perceived platform error exposure influence perceived value and behavioral intentions among university students in Indonesia and Malaysia. Drawing on the Information Systems Success Model, SERVQUAL, and post-adoption continuance theory, an extended structural equation modelling framework was tested using cross-sectional survey data from 123 undergraduate students, comprising 62 respondents from Indonesia and 61 from Malaysia. The sample included LMS users (69.9%) and MOOC users (30.1%). Data were analyzed using confirmatory factor analysis and SEM in IBM AMOS. The measurement model showed good fit: χ²/df = 1.74, CFI = 0.961, TLI = 0.954, RMSEA = 0.048, and SRMR = 0.042. In the extended model, service quality positively predicted perceived value (β = 0.593, p < 0.001) and behavioral intentions (β = 0.481, p < 0.001), while perceived value positively predicted behavioral intentions (β = 0.391, p < 0.001). Perceived platform error exposure negatively predicted perceived value (β = −0.314, p < 0.001), and perceived value significantly mediated the service quality–behavioral intention relationship (β = 0.232, p < 0.001). The extended model explained 59.8% of the variance in perceived value and improved model fit relative to the baseline model. These findings position platform error exposure as a distinct negative user-experience construct and highlight the need to improve service quality while reducing recurring technical failures.